2017
DOI: 10.4103/lungindia.lungindia_205_16
|View full text |Cite
|
Sign up to set email alerts
|

Study of oxidative stress biomarkers in chronic obstructive pulmonary disease and their correlation with disease severity in north Indian population cohort

Abstract: Background:Oxidant-antioxidant imbalance forms a prime component in pathogenesis of chronic obstructive pulmonary disease (COPD). Studies of oxidative stress markers in South Asians were sparse.Methods:One hundred and eighty COPD patients and eighty healthy nonsmokers were enrolled in the study. Serum malondialdehyde (MDA) and iron levels were estimated for oxidative stress. Three antioxidant markers evaluated-catalase, superoxide dismutase (SOD), and serum copper. Patients on antioxidant therapy and with seps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Jyoti Bajpai et al , Study of Oxidative Stress Biomarkers and their correlation with disease severity. [ 4 ] This is generally consistent with prior data and adds to the limited data on this subject from India. While the study also reports significant differences in oxidant/antioxidant markers between COPD and nonsmoking healthy controls, these differences can be attributed to either smoking or COPD.…”
supporting
confidence: 89%
“…Jyoti Bajpai et al , Study of Oxidative Stress Biomarkers and their correlation with disease severity. [ 4 ] This is generally consistent with prior data and adds to the limited data on this subject from India. While the study also reports significant differences in oxidant/antioxidant markers between COPD and nonsmoking healthy controls, these differences can be attributed to either smoking or COPD.…”
supporting
confidence: 89%
“…MDA is one of the oxidative stress biomarkers, 18 and it has been shown that there is an association between serum levels and COPD severity. 19 , 20 The serum samples of patients were first heated with thiobarbituric acid under acidic conditions according to the instructions provided by the kit manufacturer and then cooled down. Afterward, the resulting color combination in n-butanol was extracted.…”
Section: Methodsmentioning
confidence: 99%
“…MDA is one of the most commonly used representative indicators of OS injury ( 13 ). It is able to activate Kupffer cells to secrete numerous cytokines, activate hepatic stellate cells (HSC), and mediate HSC differentiation, proliferation and collagen synthesis ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is able to activate Kupffer cells to secrete numerous cytokines, activate hepatic stellate cells (HSC), and mediate HSC differentiation, proliferation and collagen synthesis ( 22 ). Another indicator of OS injury is SOD, which scavenges ROS, a representative of the body's antioxidant system ( 13 ). The increased/decreased levels of MDA/SOD in the experimental vs. those in the control group indicated that the hepatic vein occlusion induced intra- and extrahepatic lipid peroxidation injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation